Effectiveness of Jumping Rope Exercise Verses Short Foot Exercise on Pain and Quality of Life for Subjects with Flat Foot. - Preethi K.; Kamalakannan M.; Anitha A.; Ramana K. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Pes planus, commonly known as flat foot, is a deformity that leads to the collapse of the medial longitudinal arch and flattening of the foot against the ground. This study aims to compare the effectiveness of jumping rope exercise and short foot exercise on pain reduction and improvement in quality of life for patients with flatfoot. Purpose: To find out the effect of Jumping rope exercise versus short foot exercise among individuals with flatfoot. Method: A sample of 30 participants who met the inclusion and exclusion criteria were selected for the study. They were divided into two groups: the jumping rope exercise group with ultrasound (n=15) and the short foot exercise group with ultrasound (n=15). The interventions were administered five times a week for three weeks. The entire process was performed from November 2022 to April 2023. Outcome measure: The navicular drop test (NDT) was used to measure the degree of foot pronation, the Numeric Pain Rating Scale (NPRS) was employed to assess pain levels, and the Foot Health Status Questionnaire (FHSQ) was utilized to evaluate participants' quality of life. Results: The mean value of the jumping rope exercise group at the post-test was significantly higher than that of the short foot exercise group, with a p-value of <0.0001 Conclusion: Based on the findings, it can be concluded that jumping rope exercise with ultrasound therapy yields superior outcomes in managing Pes Planus compared to short foot exercise.